2017
DOI: 10.1111/jpn.12858
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic acids or probiotics alone or in combination on growth performance, nutrient digestibility, enzyme activities, intestinal morphology and gut microflora in broiler chickens

Abstract: A feeding trial was conducted to determine the effect of organic acids or probiotics alone or in combination on growth performance, nutrient digestibility, enzyme activity, intestinal morphology and gut microflora in broiler chickens (Ross308). A completely randomized design was used, with 1,440 broiler chicks across four treatments and five replications of 72 chicks each. The chicks in the control treatment were fed on a control diet (CD), whereas for the other treatment groups, the CD was supplemented with 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 58 publications
5
56
0
1
Order By: Relevance
“…This present finding was in accordance with Agboola et al (2015), who documented that dietary supplementation of organic acid (formic and propionic acids), probiotics (Lactobacillus sporogenes and Saccharomyces cerevisiae) or the blends of both increased villi height and crypt depth of broiler intestine. Similarly, Rodjan et al (2018) showed that feeding the blends of organic acid and probiotics resulted in higher duodenal villi height and crypt depth when compared with control. Considering the essential role of villus and crypt in the absorption process, our findings therefore suggested that fermented A. bilimbi L. fruit filtrate improved the absorptive capacity of experimental broilers.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This present finding was in accordance with Agboola et al (2015), who documented that dietary supplementation of organic acid (formic and propionic acids), probiotics (Lactobacillus sporogenes and Saccharomyces cerevisiae) or the blends of both increased villi height and crypt depth of broiler intestine. Similarly, Rodjan et al (2018) showed that feeding the blends of organic acid and probiotics resulted in higher duodenal villi height and crypt depth when compared with control. Considering the essential role of villus and crypt in the absorption process, our findings therefore suggested that fermented A. bilimbi L. fruit filtrate improved the absorptive capacity of experimental broilers.…”
Section: Discussionmentioning
confidence: 91%
“…The mechanism by which the fermented fruit filtrate reduced intestinal population of Enterobacteriaceae was not exactly known, but it seemed that the presences of organic acids and lactic acid were responsible for the antibacterial activity of the fermented fruit filtrate. Rodjan et al (2018) noticed that dietary supplementation of organic acids, probiotics, or combination of both improved the intestinal bacterial ecology by decreasing intestinal population of Escherichia coli and increasing lactic acid bacteria counts. Yet, our treatment did not substantially affect the population of lactic acid bacteria in the intestine of experimental broilers, which was in accordance to Agboola et al (2015) showing no effect of organic acids, probiotics, or combination of both on intestinal lactic acid bacteria counts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, microscopes were used to observe the samples, and computer-aided systems were used to photograph the samples. Finally, an image analysis system was used to measure villi length and crypt length [23,24].…”
Section: Animal Management and Samplementioning
confidence: 99%
“…The use of probiotics in broiler diets is a strategy that can improve diversity and stability of the intestinal microbiota, immunomodulation, competition for adhesion sites and the production of antimicrobial agents resulting in improved broiler performance (12)(13)(14) . In addition, accumulating studies indicate that probiotics exert beneficial effects on body anti-oxidative capacity, digestive enzymes and nutrient absorption and decrease cell apoptosis, which finally favours the gut health and production performance of broilers (15)(16)(17)(18) . Among many bacterial species used as probiotics, spore-forming Bacillus spp.…”
mentioning
confidence: 99%